Logistics and Supply Chain Management - Samal , Sarat K (International Journal of Psychosocial Rehabilitation, 2019)
This paper discusses various aspects of logistics and supply chain management, such as the benefits of a full logistics model and supply chain management. It also outlines a series of challenges in logistics and supply chain management. Technology has been regarded as an enabler for current supply chain and logistics processes to develop. Recent trends in culture and industry, however, such as mobile computing, social media, and online retailing, have changed almost every part of the supply chain and logistics environment significantly. In particular, it analyses ISOFT Australia’s logistics and supply chain model-a computer and video game publisher. It points out some potential problems of Ubisoft Australia with the software system, communication and information flow in inbound logistic and non-conforming returns by conducting interviews and observations together with gathering company internal records. Eventually, a number of proposals are being made for further changes. Supply chains are now being used to support business strategies within an organization. Several organizations accept their supply chain as being a key business method versus a cost centre. Networks of distribution evolve from centralized to distributed, and then to hybrid. Businesses are also using logistics and transportation in multimode rather than a single mode. Nevertheless, in addition to the channel distribution, more businesses are delivering directly to their customers.